Niveles de ventas en la Lavadora y Lubricadora Sulay del Cantón Montalvo, en el periodo 2022-2023 - Diaz Solano, Isamar Verania (2023)
The purpose of this case study entitled “Sales levels in the Sulay washing machine and lubricator in the Montalvo canton, in the period 2022-2023” is to analyze the level of sales, through the comparison of sales reports, SWOT analysis, which will allow us to propose strategies to increase the growth of the company. Given its nature, this work is related to the line of research: Financial, administrative, tax management, auditing and control, and is part of the subline of public and private companies and institutions. The identified problems were determined through the root-cause analysis method, since it gave rise to identifying and delving into the origin of the problems that affect the sales of the business, taking into account the techniques used which were SWOT analysis and matrix. comparative. The results that were obtained allowed us to analyze the factors that are causing shortcomings in the growth and sales level of the company. Giving way to proposing sales strategies in the form of recommendations.